Implementasi Kebijakan Program Peternakan Rakyat sebagai Wahana Pengembangan Modal Sosial di Kabupaten Kuantan Singingi - Saam, Zulfan (Jurnal Ilmu Administrasi Negara, 2009)
Sociocultural values, are actually social capital in development but the government hasless attention to them especially in the implementation of the development programs of the villagecommunity. The community group of the collective herding in Kuantan Singingi Regency has a bigrole in implementing of the government assistance funds to the village community. The collectiveactivities have been patterned in cultural values which would be the social capital in developmentprogram. This study aims to know the cultural values in the collective herding group and how farthese values can be applied and improved in the implementation of the development program andthe usage of the village community ability efficiently. This study is a qualitative research. Data arecollected through dept interviewing with the key informans including the chief collective herdingand the community figures, observation and documenter. The result of this study shows that thecultural values which are called the local wisdom concept can hold out and be developed in support-ing of the implementation of the government assistance funds for improving the prosperity of thevillage community.